New player on the scene: Turkish engagement in Africa. - Rudincová, Kateřina (Bulletin of Geography. Socio-economic Series, 2014)
Turkey's engagement in Africa is connected to the ideological shift of Turkish government during the era of Justice and Development Party and its redirection from the Western-centred to the more diversified foreign policy. Turkish policy in Africa has two dimensions: first one is promoted by the official representation of the State, and the second is performed mainly by civil sector of Turkish society, the business organisation as well as various NGOs. This paper examines Turkish involvement in Africa from various perspectives. It focuses on the economic, political as well as ideological role of Turkey in Africa.